The Impact of Health Education Programs for Pregnant Women on the Reduction of Maternal and Infant Mortality - Nurhidayati; Yayuk Sri Rahayu; Dewi Rubi Fitriani; Ni Nyoman Murti; Grace Carol Sipasulta (Miracle Journal Get Press, 2025)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) remain major health challenges in developing countries, driven by socioeconomic disparities, limited education, and poor healthcare access. Lack of knowledge about prenatal care is a key factor. This review examines the impact of health education on reducing maternal and infant mortality and provides evidence to support stronger health programs and policies.Findings show that health education enhances pregnant women’s knowledge, attitudes, and practices related to pregnancy and infant care. Prenatal checkups help detect anemia, malnutrition, hypertension, and infections, allowing early intervention. Education also reduces anxiety, supports mental health, and improves birth outcomes.Despite its benefits, implementation faces barriers such as limited resources, insufficient healthcare personnel, poor access in remote areas, and cultural or socioeconomic constraints.In conclusion, health education is an effective strategy to reduce maternal and infant mortality. Developing culturally appropriate, sustainable, and accessible programs is essential to strengthen maternal services and improve outcomes for mothers and infants.